2019
DOI: 10.1002/jcp.28069
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Nrf2 promotes the antitumor effect of Pinelliae rhizome in papillary thyroid cancer

Abstract: We previously reported that Xiaotan Sanjie (XTSJ) decoction can prevent the progression of gastric cancer in vitro and in vivo. Pinelliae rhizome (PR), one component of XTSJ decoction, has an inhibitory effect on the growth and proliferation of tumor cells. The present study investigated the underlying mechanisms of action of PR. Using the human papillary thyroid cancer cell lines, TPC‐1 and BCPAP, we found that XTSJ decoction and PR alone decreased cell viability to a similar extent in both cell lines, wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…The nuclear Nrf2 accumulates and binds with antioxidant reaction pieces promoting cytoprotective gene transcriptions involving antioxidant, antitoxic, and anti-inflammatory actions. 78 Nrf2 plays an important role in the thyroid gland, it promotes the transcription and protein synthesis of antioxidant and cytoprotective molecules. It protects against intra-thyroidal oxidative damage and prevent excessive iodination.…”
Section: Discussionmentioning
confidence: 99%
“…The nuclear Nrf2 accumulates and binds with antioxidant reaction pieces promoting cytoprotective gene transcriptions involving antioxidant, antitoxic, and anti-inflammatory actions. 78 Nrf2 plays an important role in the thyroid gland, it promotes the transcription and protein synthesis of antioxidant and cytoprotective molecules. It protects against intra-thyroidal oxidative damage and prevent excessive iodination.…”
Section: Discussionmentioning
confidence: 99%
“…In mice orthotopically transplanted with a PTC cell line, the combination of Nrf2 knockdown in the PTC cells before transplantation and PR treatment of the animals significantly decreased the tumor burden and extended the survival of the animals. In contrast, when the PTC cells were transplanted into the thyroids of Nrf2 KO mice, the tumor burden was increased, survival was shortened, and the protective effect of PR treatment was lost [70]. Taken together, the findings of the aforementioned recent studies further support the original concept that the Nrf2 pathway is activated in PTC and has a protective effect in thyroid carcinoma cells [63].…”
Section: Thyroid Carcinomasmentioning
confidence: 63%
“…In two PTC cell lines, knockdown of LUCAT1 decreased Nrf2 mRNA expression levels and Nrf2 protein abundance, while at the same time it reduced cell proliferation and invasion, and induced cell-cycle arrest and apoptosis [69]. Lastly, another study showed that Pinelliae rhizome (PR), a component of a traditional medicine decoction, decreased the protein abundance of Nrf2 in the nucleus of PTC cell lines in a dose-dependent manner, and decreased their viability [70]. Knockdown of Nrf2 via small interfering RNA (siRNA) in the PTC cell lines decreased their viability and had an additive or synergistic effect with PR.…”
Section: Thyroid Carcinomasmentioning
confidence: 99%
“…Pinellia ternata Eliminating phlegm, inhibiting the secretion of gastric juice, increasing the activity of tyrosine transaminase, promoting bile secretion, antivomiting, and antitumor effect (Du et al, 2019) Citri Reticulatae Pericarpium…”
Section: Core Herb Name Pharmacological Actionsmentioning
confidence: 99%